Evaluating Executive Functions: Planning Strategies in Students with Dyscalculia: An Applied Study on a Sample of Third-Grade Primary Students - DEKKICHE, Saadia; BENABDELMALEK, Abdelaziz (Journal of Human Sciences, 2025)
This study aims to evaluate a fundamental executive function, specifically the planning strategy, in third-grade primary students diagnosed with dyscalculia. Utilizing a case study approach, a deliberately chosen sample of five (5) students, ages 8 to 9 and identified with dyscalculia, was analyzed. For hypothesis validation, diagnostic subtests from the Zareki R battery and the complex Figure de Rey test were employed. The outcomes revealed the presence of significant planning strategy disorders among the dyscalculic students. In light of these findings, it is recommended that further research be conducted to explore executive functions, particularly the planning strategy, within dyscalculic student populations to enhance their academic resilience and address the educational challenges posed by dyscalculia.